Community Empowerment Through Sulfur Soap Preparation for Dermatitis Prevention - Amirah Adlia; Sakinah Aljuffrie; Annis Catur Adi; Deandra Ardya Regitasari; Vidya Anggarini Rahmasari; Heni Rachmawati (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: As a country with a tropical climate, Indonesia has the risk to have many disease problems, such as skin disorder or dermatitis. Dermatitis is an either acute, sub-acute, or chronic inflammatory skin disease. One of therapies is using sulfur compound. Purpose: The objective of this program was to improve public awareness of Tulungagung Regency on the importance of health care, to train people preparing soap containing sulfur, and to help the people to empower the economic community through home industry initiation. Methods: This program was done by motivation generating, counseling, advocacy, and education. The activities were performed through counseling about skin diseases, causes, the prevention and treatment of the disease with sulfur soap, demonstration and providing training to the community about sulfur soap. Results: The training on handmade soap preparation was conducted at the Village Hall of Mojosari, Kauman, Tulungagung, on July 28-29th 2019 and was attended by 20 female participants. The socialization programme was carried out by providing technical guidance, visual exposure of materials, packaging training through small groups. Conclusion: This training program of soap containing sulfur preparation attracted public attention to gain the science, knowledge, and skill increase business motivation, knowledge, and community skills as well as motivation generation to apply a simple technology of soap containing sulfur manufacturing.